2010
DOI: 10.3382/ps.2010-00888
|View full text |Cite
|
Sign up to set email alerts
|

A single nucleotide polymorphism in the parathyroid hormone gene and effects on eggshell quality in chickens

Abstract: Parathyroid hormone (PTH), released by the parathyroid gland of animals, plays an important role in regulating the metabolism of calcium and phosphate. As a candidate gene for eggshell quality traits, the SNP was screened and its genetic effects on eggshell qualities and levels of serum calcium, phosphate, and PTH were analyzed in this study. Three hundred Houdan hens, an indigenous breed of chicken in France, were used for genotyping and data recording. Of the 3 sets of primers used to amplify the exons, exon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
1
6
0
2
Order By: Relevance
“…Also, Preda et al 2013found that higher production of eggs induces an increase in the plasma concentration of calcium. The obtained results of increasing plasma Ca , Ph and PTH levels related to the increase of Ca and Ph levels in eggshell (Table 3) and eggshell quality (Table 2) and OPN concentration (Table 1) are in harmony with those previously mentioned by Jiang et al (2010) and Preda et al (2013) who found that the increase of PTH concentration was parallel with the plasma calcium level and PTH controls Ca and Ph level of blood and maintains the Ca homeostasis by regulating Ca liberation from the bone. Furthermore, Noda and Rodan (1989) and Lavelin et al (2000) revealed that calcitrophic substance such as PTH hormone had regulation effect on OPN gene expression.…”
Section: Statistical Analysessupporting
confidence: 85%
See 1 more Smart Citation
“…Also, Preda et al 2013found that higher production of eggs induces an increase in the plasma concentration of calcium. The obtained results of increasing plasma Ca , Ph and PTH levels related to the increase of Ca and Ph levels in eggshell (Table 3) and eggshell quality (Table 2) and OPN concentration (Table 1) are in harmony with those previously mentioned by Jiang et al (2010) and Preda et al (2013) who found that the increase of PTH concentration was parallel with the plasma calcium level and PTH controls Ca and Ph level of blood and maintains the Ca homeostasis by regulating Ca liberation from the bone. Furthermore, Noda and Rodan (1989) and Lavelin et al (2000) revealed that calcitrophic substance such as PTH hormone had regulation effect on OPN gene expression.…”
Section: Statistical Analysessupporting
confidence: 85%
“…Furthermore, Noda and Rodan (1989) and Lavelin et al (2000) revealed that calcitrophic substance such as PTH hormone had regulation effect on OPN gene expression. Moreover, Jiang et al (2010) cleared that better eggshell quality and breaking strength could be due to the higher blood Ca, OPN and PTH. Bone strength: It is clear from Figure 3 that the tibia bone of embryos at day 15 and hatched chicks are stronger(p≤0.05) for M chicken strain than those for G one.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The metabolism of calcium is regulated by several main hormones, such as PTH, calcitonin, stanniocalcin, estrogens, and thyroid hormone . Therefore, these hormones may influence avian eggshell strength by regulation of calcium metabolism, and the associations between PTH gene and eggshell quality have been discovered . Our present study suggests TTR and RBP4 should be paid more attention for their association with eggshell quality.…”
Section: Resultsmentioning
confidence: 59%
“…This SNP caused a missense mutation resulting in a change from histidine to arginine. Importantly, these three SNP (rs313064671, rs317191671, and rs316353058) of the OC-116 gene were in the conserved domain (http://asia.ensembl.org/Gallus_gallus/Transcript/ Domains), suggesting that these SNPs may alter the structure of the conserved domain and affect protein function during the initial phase of shell mineralization (Jiang et al, 2010).…”
Section: Ovocleidin-116mentioning
confidence: 99%